Implementasi System Captive Portal Dengan Otentikasi RADIUS - Fandi Ali Mustika; Febryo Ponco Sulistyo; Chairul Anhar Tanof (Jurnal Ilmiah FIFO, 2020)
Abstract The rapid development of Internet networks in offices, industries, homes, and universities, transforming the conventional system into modern, especially with the Internet. Therefore, it is very important to use a good authentication method to avoid unauthorized user access. Wireless network without authentication can harm users in their activities using Internet access. One of the most effective ways for secure wireless network authentication with Captive portals with Radius authentication method. Captive portals are web pages that control Hyper Text Transfer Protocol (HTTP) browser access to the Internet. The user who is in authentication is their MAC address. Radius is a service that authenticates and authorizes users to network and network infrastructure. This paper will discuss how to use RADIUS authentication with captive portals to manage user authentication on wireless networks. Built-in security mechanism in Wifi 802.11.x equipment to control who can associate to an Access Point (AP). The use of captive portal so that the AP works without configuration settings, so it does not burden the work of the AP itself.Keywords: Captive Portal, Radius, Authentication, Wireless Network Abstrak Perkembangan jaringan internet yang semakin pesat di kantor, industri, rumah, dan universitas, mengubah sistem konvensional menjadi modern, terutama dengan adanya internet. Oleh karena itu, sangat penting untuk menggunakan metode otentikasi yang baik untuk menghindari akses pengguna yang tidak sah. Wireless network tanpa otentikasi dapat membahayakan pengguna dalam aktivitas mereka dalam menggunakan akses internet. Salah satu cara yang paling efektif untuk otentikasi wireless network yang aman dengan Captive Portal dengan metode otentikasi Radius. Captive portal adalah halaman web yang mengkontrol Hyper Text Transfer Protocol (HTTP) akses browser ke internet. Pengguna yang di otentikasi adalah MAC address mereka. Radius adalah layanan yang mengotentikasi dan mengotorisasi pengguna ke jaringan dan infrastruktur jaringan. Mekanisme keamanan built-in di peralatan Wifi 802.11.x untuk mengontrol siapa saja yang dapat berasosiasi ke Access Point (AP). Penggunaan captive portal agar AP bekerja tanpa seting konfigurasi, sehingga tidak membebani kerja dari AP itu sendiri.Kata Kunci: Captive Portal, Radius, Otentikasi, Wireless Network